Small vessel occlusion and syphilis in patients with first-ever ischemic stroke - Matheus Gomes Ferreira; Valeria Cristina Scavasine; Giovanni Luís Breda; Bernardo Montesanti Machado de Almeida; Viviane de Hiroki Flumignan Zétola; Marcos Christiano Lange (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Syphilis is an endemic disease, particularly in low- and middle-income countries, with vascular involvement in large vessels (aortitis), but no clear relationship with stroke patients, except for those who presented with meningovascular neurosyphilis. Objective: To investigate the relationship between a positive history of syphilis determined by serological testing and ischemic stroke etiology, particularly small vessel disease (SVD). Methods: In total, 269 first-ever ischemic stroke patients admitted to the stroke unit were tested for syphilis. Patients with neurosyphilis were excluded. All patients were classified according to the ASCOD phenotyping as SVD — when SVD was the potential causal mechanism (S1) — or non-SVD — when SVD was uncertain (S2), unlike (S3), or not detected (S0). Results: Syphilis was positive in 32 (12%) patients. When comparing patients with positive and negative serology, the only significant difference was SVD as the causal mechanism (S1) in patients with positive results: 9 (28%) vs. 22 (9%), p<0.01. Conclusion: The current study showed that the frequency of positive syphilis serological test was higher in patients with first-ever ischemic stroke and SVD as the potential causal mechanism. This finding could be related to the endothelial dysfunction occurring in syphilis.